Intersex gender determination in classical Islamic law and modern medicine: an analysis for Integration - Mohd Badrol, Muhammad Afif; Awang, Abdul Bari; Haneef, Sayed Sikandar Shah (International Islamic University Malaysia (IIUM), 2018)
Intersexuality is a biological fact of human birth. Unlike the normal birth of human species as boys and girls, instances of babies born with ambiguous sexual denomination has been part of human procreation since time immemorial. In the context of Islam, Islamic law contains both regular laws and special provisions dealing with this genre of humans. In the process, the most perplexing issue facing classical jurists was juridical determination of intersexuality in order to decide which set of laws can apply on an intersex. Therefore, they formulated their own juridical criteria and set of indicators mainly dealing with the appearance of genitalia at birth and its function during infancy, otherwise postponing their judgments until the exhibition of secondary characteristic by such individuals. Modern medical science changed the landscape by examining not only the external genitalia but also internal sexual system and chromosomal formula to assign a particular gender to an intersex. This study after delineating the position in both fiqh and medicine argue for regulated integration between the two.